Parenting Promotes Social Mobility Within and Across Generations - Jorge Luis García; James J. Heckman (Institute of Labor Economics (IZA), 2022)
This paper compares early childhood enrichment programs that promote social mobility for disadvantaged children within and across generations. Instead of conducting a standard meta-analysis, we present a harmonized primary data analysis of programs that shape current policy. Our analysis is a template for rigorous syntheses and comparisons across programs. We analyze new long-run life-cycle data collected for iconic programs when participants are middle-aged and their children are in their twenties. The iconic programs are omnibus in nature and offer many services to children and their parents. We compare them with relatively low-cost more focused home-visiting programs. Successful interventions target both children and their caregivers. They engage caregivers and improve the home lives of children. They permanently boost cognitive and non-cognitive skills. Participants in programs that enrich home environments grow up with better skills, jobs, earnings, marital stability, and health, as well as reduced participation in crime. Long-run monetized gains are substantially greater than program costs for iconic programs. We investigate the mechanisms promoting successful family lives for participants and find intergenerational effects on their children. A study of focused home-visiting programs that target parents enables us to isolate a crucial component of successful programs: they activate and promote parenting skills of child caregivers. The home-visiting programs we analyze produce outcomes comparable to those of the iconic omnibus programs. National implementation of the programs with long-run follow up that we analyze would substantially shrink the overall US Black-White earnings gap.
Keywords: J18; J13; J24; J31; D13; 330; skills; social mobility; inequality; human development